Exploring Factors Affecting The Auditor’s Organizational Commitment in The Government Organization - Indah Triyani; Eko Tama Putra Saratian (Universitas Mercu Buana, 2021)
This study aims to analyze the influence of Quality of Work Life, Role Conflict and Job Satisfaction on Auditor’s Organizational Commitment in the Government Organization. The populations in this study were 80 Auditors of Government Organization. The sample used was 80 respondents in the division of the Deputy State Accountant in the Government Organization. The sampling method uses saturated sampling technique. Design of this research is quantitative method with questionnaires for data collection. This research using Structural Equation Modeling with Part Least Square (SEM-PLS) version 3.0. The results of the research shows that Quality of Work Life has a positive and significant effect on Organizational Commitment, Role Conflict has a not significant negative effect on Organizational Commitment, and Job Satisfaction has a positive and significant effect on Organizational Commitment. This research will contributed to institutions particularly in the Human Resources Division. Further researchers can also conduct research with the object of the Auditor in private institutions, so that the results can be compared.